Produksi Rekombinan Bovine Lactoferrin pada Sistem Ekspresi Eschericihia coli - Mirayanti, Ni Luh Wayan Yulia; Mahardika, I Gusti Ngurah Kade; Pharmawati, Made (Jurnal Veteriner; Vol 23 No 1 (2022), 2022)
Lactoferrin is an 80 kDa glycoprotein which has advantages in biological activity as an antimicrobial, antibacterial, antiviral, antiparasitic, and immunomodulatory agent. Advances in recombinant technology have made it possible to produce lactoferrin proteins on a large scale, the production of recombinant lactoferrin can be carried out in various expression systems. Escherichia coli is one of the hosts in expression systems that are widely used in the production of recombinant proteins. The recombinant protein lactoferrin is produced by insertion of the bovine lactoferrin gene in the plasmid pET 11-a. The bovine lactoferrin gene that has been inserted into the plasmid pET, transformed and expressed in the cell host of E. coli BL21. The bovine lactoferrin protein expression was induced by the addition of a chaperone one of the coexpressions, which accompanied the E. coli synthesis system to achieve the desired protein expression. The expression of pET11a - Bovlacto plasmid in E. coli was supported by the inducer L-arabinose and IPTG. The bovine lactoferrin gene embedded in the recombinant plasmid pET-11a was able to be well expressed in E. coli BL21 with the hybridization signal in the dot blot method test and the target specific band, namely in the 80-85 kDa position range of SDS-PAGE electrophoresis results.